The Knowledge Level of Elderly in Karang Taliwang Village and the Incidence of Low Back Pain in 2025 - Lioni, Ni Kadek; Wedayani, Anak Agung Ayu Niti; Purnaning, Dyah; Alaydrus, Mukaddam (Jurnal Biologi Tropis, 2025)
Low Back Pain (LBP) is a prevalent musculoskeletal problem worldwide, particularly among the elderly population. This study aims to analyze the relationship between the level of knowledge among elderly individuals in Karang Taliwang Village and the incidence of LBP. A quantitative approach with a cross-sectional design was employed, using an ordinal scale to measure knowledge levels and a nominal scale for LBP incidence. The results indicate a significant relationship between knowledge levels and LBP incidence, where elderly individuals with lower knowledge levels tend to experience LBP more frequently. This study concludes that enhancing education on LBP risk factors and prevention is essential for reducing its prevalence among the elderly. The scientific implication of this study highlights the need for evidence-based educational interventions to lower LBP prevalence and improve the quality of life among older adults.